Pengaruh Tax Avoidance terhadap Kinerja Keuangan Perusahaan Manufaktur yang Terdaftar di BEI - Tsabitah Meylan Giafi; Ajeng Tita Nawangsari (AKUNTANSI 45, 2026)
nalyzing the effect of tax avoidance on the financial performance of manufacturing companies from 2019 to 2023 is the purpose of this article. The independent variable in the form of tax avoidance is proxied with ETR, while the dependent variable is financial performance proxied through ROA. The analysis was carried out using a quantitative approach using the panel data regression method, as well as a model selection test, where the test results determined the Fixed Effect Model as the best model. The regression results show that tax avoidance has a negative effect on financial performance, but it is not partially significant. In contrast, simultaneous tests (F-tests) show that the model is significant overall. The Adjusted R² value of 93.5% indicates that the variability of financial performance can largely be explained by the model. Conceptually, these findings support the agency theory that asserts that tax avoidance practices negatively impact company performance. In addition, this study emphasizes the importance of internal supervision and transparency of financial reporting in reducing the risk of tax evasion. These findings are expected to be able to contribute to management in formulating a more optimal tax strategy, as well as for regulators in developing tax policies that are responsive and adaptive to the dynamics of the manufacturing industry.